2017
DOI: 10.4236/ojn.2017.710084
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Patient Safety in Intensive Care— A Grounded Theory

Abstract: Background: The modern intensive care unit (ICU) is a complex and high-risk environment, and even small adverse events and changes may deteriorate the patient's conditions and eventually cause harm. Many factors can potentially be associated within an increased amount of errors, leading to adverse events. Nurses, nurse managers, and other leaders all play important roles in establishing patient safety. Aim: This study aimed to obtain a deeper understanding of leaders' and nurses' main concerns in establishing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
(32 reference statements)
1
0
0
Order By: Relevance
“…We also found inter‐professional interactions as a contextual factor affecting the ER process. This is in line with the findings of a former study which reported that trust and respect among healthcare providers enhance their satisfaction, improve their sense of responsibility towards patients, promote their involvement in care delivery, and thereby, improve patient safety and care quality (Häggström et al, 2017 ). Inter‐professional collaboration and interactions not only improve staff's satisfaction and reduce their stress but also promote their adherence to patient safety standards (Vaismoradi et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…We also found inter‐professional interactions as a contextual factor affecting the ER process. This is in line with the findings of a former study which reported that trust and respect among healthcare providers enhance their satisfaction, improve their sense of responsibility towards patients, promote their involvement in care delivery, and thereby, improve patient safety and care quality (Häggström et al, 2017 ). Inter‐professional collaboration and interactions not only improve staff's satisfaction and reduce their stress but also promote their adherence to patient safety standards (Vaismoradi et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%